Outcomes in Emergency Department Patients with Dyspnea versus Chest Pain: A Retrospective Consecutive Cohort Study - Erik Jemt; Magnus Ekström; Ulf Ekelund (Emergency Medicine International)
Dyspnea and chest pain are major and important causes of contact at the emergency department (ED). Dyspnea is associated with high morbidity and mortality, but data on characteristics and outcomes compared with chest pain in the ED are limited. This was a retrospective cohort study of consecutive patients with contact causes of dyspnea or chest pain at two Swedish EDs from 2010 to 2014. Hospital admittance, ED revisits, and mortality were analyzed using multivariable regression models, adjusted for ED and markers of disease severity (age, sex, centre, Charlson comorbidity index, c-reactive protein, troponin T, and arrival by ambulance). 29,291 patients (mean age 58.3 years; 48.9% women) with dyspnea (n = 8,812) or chest pain (n = 20,479) were included. Dyspnea patients were older than patients with chest pain (64 vs. 56 years, p<0.001) and had more comorbidity and higher average blood troponin T and c-reactive protein levels. Dyspnea patients also had higher hospitalization rates (48% vs. 30%; adjOR (95% CI) 2.1–2.3), including the intensive care unit (1.4% vs. 0.1%; adjOR 6.9–15.9), and more ED revisits (11% vs. 7%; adjOR 1.2–1.7) in 30 days. Dyspnea patients had five-fold increased mortality compared to those with chest pain; hazard ratio (HR) 5.1 (4.8–5.4), adjusted for markers of disease severity, the mortality was two-fold higher, HR 2.2 (2.0–2.4). Compared with chest pain patients, ED dyspnea patients are older, have more comorbidity, and have worse outcomes in terms of hospitalization, morbidity, and mortality.